Práticas agroecológicas na transformação de paisagens - AVIZ, Larissa Beatriz da Silva (Universidade Federal do Pará, 2023)
This dissertation aimed to analyze how the agroecological practices, developed by the farmers of the Group for Agroecological Consumption, contribute to the transformation of the landscape and the constitution of socioagrobiodiversity. To achieve the proposed objective, the research, of qualitative approach, was carried out through field research with participant observation. In order to understand the farmers' ways of life and their relationship with natural resources, I adopted the cinematographic record of exploration. The analyses took place based on two stages that complement each other: satellite images and the life history of farmers in order to understand the changes in the landscape. The results of this work show that the agroecological practices of GRUCA’s farmers are alternatives for transforming landscapes degraded by predatory economic activities into agrobiodiverse landscapes. These farmers have, in their history, the presence of peasant agriculture, in such a way that some present a continuity of peasant agriculture; others, of resumption, while others have found, in agriculture, an alternative way of life. It is also noteworthy that the farmers' agroecological practices were perfected based on their life trajectories, interaction with natural, technical, and financial resources, and a network of people and social movements available in the territory. This perspective is reflected in the diversity of practices and also of landscapes.